Addressing Climate Change Vulnerability in the IUCN Red List of Ecosystems—Results Demonstrated for a Cross-Section of Major Vegetation-Based Ecosystem Types in the United States - Patrick J. Comer; Jon C. Hak; Patrick McIntyre (Land, 2022)
The IUCN Red List of Ecosystems (RLE) is a global standard for ecosystem risk assessment that integrates data and knowledge to document the relative risk status of ecosystem types as critically endangered (CR), endangered (EN), and vulnerable (VU). A series of indicators for each type gauge the probability of range wide “collapse”. Climate change vulnerability can factor into RLE assessments, especially as indicators of climate change severity under the criteria for environmental degradation over the recent and upcoming 50 years. We applied a new framework to assess climate change vulnerability—and thus, severity of climate change degradation—to a cross-section of 33 upland ecosystem types in the United States to demonstrate this input to the RLE. The framework addressed climate exposure and ecosystem resilience. Measures of climate change exposure used climate projections for the mid-21st century compared against a 20th century baseline. Augmenting measures in use for RLE assessment, measures of resilience included several for adaptive capacity, including topoclimate variability, diversity with functional species groups, and vulnerability of any keystone species. All 33 types were listed as VU (n = 22), EN (n = 9), or CR (n = 2) and 51% scored at least one step higher (e.g., LC up to VU) from climate change severity.